Effects of elevated CO2 and temperature on survival and wing dimorphism of two species of rice planthoppers (Hemiptera: Delphacidae) under interaction. Issue 6 (31st January 2020) - Wang, Caiyun; Fei, Minghui; Meng, Ling; Harvey, Jeffrey A; Li, Baoping
Abstract: BACKGROUND: Anthropogenic climate change (ACC) may have significant impacts on insect herbivore communities including pests. Two of the most important climate‐change related factors are increased atmospheric concentrations of carbon dioxide (CO2 ), and increasing mean global temperature. Although increasing attention is being paid to the biological and ecological effects of ACC, important processes such as interspecific interaction between insect herbivores have been little explored. Here, in a field experiment using the FACE (free‐air CO2 enrichment) system, we investigated the effect of elevated CO2 and temperature on survival and wing dimorphism of two species of rice planthoppers, Laodelphax striatellus and Nilaparvata lugens under interaction. RESULTS: The two species were grouped into five treatments of relative density (0/50, 13/37, 25/25, and 37/13, 50/0), each of which was allocated to one of a factorial combination of two CO2 concentrations and two temperature treatments (elevated and ambient levels). Our results revealed that climatic treatment has no effects on survivorship of interspecific competing planthoppers. However, climatic treatment affected wing‐form of planthoppers under interspecific interaction. For females of N. lugens, in the 37/13 ratio, proportion macropterours form was lower under elevated CO2 + temperature than under the ambient environment or than under elevated temperature. For females of L. striatellus, proportion macropterous form did not differ among climatic treatments at each ratio treatment. CONCLUSION: These findings illustrate that climate change‐related factors, by affecting the macropetry of interspecific competing planthoppers, may influence planthopper fitness. We provide new information that could assist with forecasting outbreaks of these migratory pests. © 2020 Society of Chemical Industry Abstract : Elevated CO2 and temperature have no effects on survivorship of interspecific interaction planthoppers. However, climatic treatment affects wing‐form of planthoppers under interspecific interaction. © 2020 Society of Chemical Industry